2020
DOI: 10.3324/haematol.2019.241208
|View full text |Cite
|
Sign up to set email alerts
|

Cell free circulating tumor DNA in cerebrospinal fluid detects and monitors central nervous system involvement of B-cell lymphomas

Abstract: Cell free circulating tumor DNA in cerebrospinal fluid detects and monitors central nervous system involvement of B-cell lymphomas. Abstract word count: 250 Text word count: 2898 Tables and figures: 5 Supplemental files: 2Acknowlegements: The authors would to thank the patients diagnosed at the Vall d'Hebron University Hospital that were enrolled in the study, as well as the Cellex Foundation for providing research facilities and equipment. ABSTRACTThe levels of cell free circulating tumor DNA (ctDNA) in plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 30 publications
3
52
1
Order By: Relevance
“…As it was shown in other CNS malignancies 18,19,21,24 , we observed that CSF is a better source for ctDNA than plasma. Interestingly, we observed that high levels of CSF ctDNA before surgical resection were detected in patients at very high risk of relapse, and disease progression was observed for two of them.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As it was shown in other CNS malignancies 18,19,21,24 , we observed that CSF is a better source for ctDNA than plasma. Interestingly, we observed that high levels of CSF ctDNA before surgical resection were detected in patients at very high risk of relapse, and disease progression was observed for two of them.…”
Section: Discussionsupporting
confidence: 81%
“…Our group and others have previously reported the detection of CSF ctDNA in adult brain malignancies [18][19][20][21][22][23] . The analysis of ctDNA in the CSF better reflects the brain tumour genomic alterations than in plasma, it can be used as a molecular diagnostic tool and the dynamic changes during patient monitoring recapitulate the disease course 18,[21][22][23][24][25] .…”
mentioning
confidence: 99%
“…This analysis also showed that tumor burden, measured by MRI or flow cytometry, was concordant with ctDNA-CSF levels but not plasma ctDNA. Moreover, ctDNA-CSF demonstrated an increased sensitivity for detecting CNS involvement compared to conventional cytology or flow cytometry (30).…”
Section: Clinical Utility In Non-glial Primary Cns Tumorsmentioning
confidence: 97%
“…In contrast, one can speculate that the use of steroids for PCNSL prior to ctDNA-CSF liquid biopsy may enhance the amount of ctDNA available in the CSF compartment. In one study 19 patients with B-cell lymphomas were evaluated to compare the utility of ctDNA-CSF or plasma in diagnosing CNS involvement and explore whether the analysis of ctDNA could monitor treatment response in CNS lymphomas (30). Genomic analysis of ctDNA from either CSF or plasma demonstrated readily detectable ctDNA-CSF in all 6 cases of CNS restricted lymphomas, while plasma ctDNA was only detected in 2 out of 6 cases, highlighting the sensitivity of ctDNA-CSF compared to plasma.…”
Section: Clinical Utility In Non-glial Primary Cns Tumorsmentioning
confidence: 99%
See 1 more Smart Citation